The Correlation Between Lipid Profile and Renal Function Tests in Patients with Cardiovascular Disease in Erbil city, Kurdistan Region of Iraq - Baqi, Hardi Rafat; K. Rostam, Shkar Rzgar (Kurdistan Journal of Applied Research, 2020)
Cardiovascular disease patients frequently suffer from the incidence of renal dysfunctions, the prevalence of the correlation, however, remains ambiguous. This study aims to see how CVD and renal function are related to the subjected group of patients suffer from symptoms of CVD. The method recruited for this objective was using of serum lipid profile test as a marker for evaluating the CVD and making correlations to the blood urea, serum uric acid, and serum creatinine levels as markers for assessing renal function on 159 individuals with CVD symptoms in Erbil city. Two statistical analysis methods (The linear regression and Pearson’s correlation) were employed for determining the existence from a lack of relationship between them. The results showed a statistically significant correlation p<0.05 by both methods between the renal function markers and TC. The UA was correlated to TG, LDL-C, and VLDL-C p<0.05 by regression analysis. The SCr was correlated to TG and LDL-C p<0.05 by both methods, and to VLDL by regression analysis. According to the outcome of the current study both lipid profile and renal function markers are correlated in mostly a statistically significant manner. Yet, the results are not conclusive, further studies are needed in this area for indemnify the irrefutable evidence concerning this relation.